Efektivitas Hipnoterapi terhadap Tingkat Anxietas dan Tekanan Darah pada Ibu Rumah Tangga dengan Penyakit Hipertensi - Indri Sarwili; Solehudin Solehudin; Maya Dwi Lestari; Inas Syabanasyah (Barongko: Jurnal Ilmu Kesehatan, 2026)
Hypertension is a major chronic health problem associated with an increased risk of cardiovascular, cerebrovascular, and renal diseases. Psychological conditions, including anxiety, may be associated with increased sympathetic activity and cardiovascular responses, potentially affecting blood pressure. Hypnotherapy is a complementary approach that may promote relaxation, reduce anxiety, and potentially influence physiological responses. This study aimed to analyze the effectiveness of hypnotherapy on anxiety levels and blood pressure among housewives with hypertension. A quantitative pre-experimental study with a one-group pretest-posttest design was conducted. Nineteen participants received hypnotherapy intervention. Anxiety levels and blood pressure were measured before and after the intervention. Descriptive statistics and the Wilcoxon signed-rank test were used because the distribution of differences did not consistently meet normality assumptions. The mean anxiety score decreased from 24.26 ± 2.70 before the intervention to 12.58 ± 2.39 after the intervention, representing a mean reduction of 11.68 points. The Wilcoxon test demonstrated a statistically significant difference in anxiety scores before and after hypnotherapy (p<0.001). Mean systolic blood pressure decreased from 144.58 ± 19.05 mmHg to 136.58 ± 20.64 mmHg, although the difference was not statistically significant (p=0.052). Mean diastolic blood pressure decreased from 91.21 ± 12.03 mmHg to 80.89 ± 10.99 mmHg, with a statistically significant difference (p=0.011). Hypnotherapy demonstrated a substantial effect on reducing anxiety and was associated with a significant reduction in diastolic blood pressure. Although systolic blood pressure decreased descriptively, the change did not reach statistical significance. Hypnotherapy may be considered a complementary intervention for anxiety management among patients with hypertension, but it should not replace standard antihypertensive treatment and risk-factor management.